Implementasi Hidden Curiculum “Tadarus” sebagai Pembentukan Karakter Mahasiswa PBSI UIN Jakarta - Saraswati, Putri; Hindun, Hindun (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This research was conducted to find out the use of hidden curriculum applied to Indonesian Language and Literature Education (PBSI) students at UIN Jakarta as character building in Educational Psychology courses. The application of hidden curiculum "tadarus" on PBSI students at UIN Jakarta, is more than just a religious activity. In addition, this activity stimulates critical thinking and reflection, helping students in the development of academic aspects, and also spiritual. The method used in this research is a descriptive qualitative research method. Before being analyzed, the data obtained is processed through observation and also distributing questionnaires to PBSI UIN Jakarta students. 11 out of 102 PBSI students were used as samples in the study. After that, the sample obtained was processed using the random sampling method. The results of this study show that there are character values possessed by UIN Jakarta students such as the value of discipline, perseverance, spiritual awareness, and this activity helps students in developing academic and religious aspects.